The impact of ultra-micro financing and local tax to life expectancy - Alit, Pijar Lintang; Suharyanto, Eko; Djamhuri, Mohammad (Jurnal Pallangga Praja (JPP), 2024)
The purpose of this research is to analyze the impacts of the implementation of fiscal policies, which include the Ultra-Micro Financing Program and Local Tax to Life Expectancy in the regencies and cities of South Sulawesi Province. The study was conducted using panel data with 138 observations derived from cross-sectional data in 23 regencies and cities in the South Sulawesi region and time series data from 2017 to 2022. The data regression model used in this research, based on testing methods and related literacy sources, is the Random Effect Model (REM). The results of this research show that all independent variables provide benefits or positive impacts on increasing the dependent variable.